(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Researchers from all across the world are very concerned about gender stereotypes in advertising. Yet, very few studies—more so in the case of India—have examined how such a communication strategy affects consumers. According to census data, women’s employment rates, educational attainment levels, and literacy rates have all increased in India. Therefore, it is crucial to evaluate customer reactions to the suitability of such a communication strategy. 450 respondents—men and women in the Delhi region between the ages of 20 and 50—were given an organized survey. Responses from customers were examined to determine the impact of female representation in marketing on the factors that include a preference for advertisements, perception of advertisements (in terms of liking and believability of the ads), attitude towards brands (in terms of liking, recall, recognition, and image of the brands), and intention. In order to determine the effect of female depictions on consumer ratings, demographic parameters were also examined. In this study, a number of hypotheses were developed and examined. To evaluate the theories, analysis of variation, the T-test, correlation, and modeling were used. The results of the research show that the representation of women in advertising is connected with advertisement like, credibility of the advertisement, company interest, acknowledgment, memory, and perception of the company, and has less of an impact on purchase intention. Fresh data on the impact of female depiction and interaction is also presented in the study. In the article, the effects on those working in marketing have also been covered(Avinash, 2016).